ANALYZING THE EFFECT OF SERVICE QUALITY AND PERCEIVED RISK ON PURCHASE INTENTION IN THE MULTIMART CONVENIENCE STORE TOMOHON CITY - Eman, Cristo .; Pangemanan, Sifrid .; Rumokoy, Farlane S. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract : Service Quality in some marketing literature has an important role as one of the strategy to win the competition. Perceived risk plays an important role to be considered as well, since the risk aversion has become a natural habit for human being. The objective of this research is to analyze the significant effect of service quality and perceived risk on consumer purchase intention simultaneously and partially. This study has conducted in Tomohon city on March â€“ April 2017. 100 customers of Multimart Tomohon were surveyed as samples. Based on the data analysis using multiple regression method, this research found that service quality and perceived risk have significances influences on consumer purchase intention simultaneously and partially. Based on that result this research recommend to Multimart Tomohon to ensure the service quality and perceived risk since both of this variable have significant influence on consumer purchase intention. Then, to continuously improving the quality in service and ease to pamper the consumers and suppliers of the product itself.Â Keywords: Consumer purchase intention, perceived risk, service quality.Â